2023
DOI: 10.1038/s41380-023-02152-6
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar disorder-iPSC derived neural progenitor cells exhibit dysregulation of store-operated Ca2+ entry and accelerated differentiation

Tristen Hewitt,
Begüm Alural,
Manali Tilak
et al.

Abstract: While most of the efforts to uncover mechanisms contributing to bipolar disorder (BD) focused on phenotypes at the mature neuron stage, little research has considered events that may occur during earlier timepoints of neurodevelopment. Further, although aberrant calcium (Ca2+) signaling has been implicated in the etiology of this condition, the possible contribution of store-operated Ca2+ entry (SOCE) is not well understood. Here, we report Ca2+ and developmental dysregulations related to SOCE in BD patient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…One showed a decrease in size of the subventricular zone in bipolar disorder organoids, compared with those derived from healthy donors. 152 In the other study, iPSC-derived human cortical spheroids of patients with bipolar disorder showed smaller size of spheroids, reduced proportion of neurons, reduced neural network activity, and decreased neuronal excitability compared with the 3D models obtained from healthy controls. 195 …”
Section: Defects In Neuronal Morphology and Interneuronal Connectivitymentioning
confidence: 84%
See 3 more Smart Citations
“…One showed a decrease in size of the subventricular zone in bipolar disorder organoids, compared with those derived from healthy donors. 152 In the other study, iPSC-derived human cortical spheroids of patients with bipolar disorder showed smaller size of spheroids, reduced proportion of neurons, reduced neural network activity, and decreased neuronal excitability compared with the 3D models obtained from healthy controls. 195 …”
Section: Defects In Neuronal Morphology and Interneuronal Connectivitymentioning
confidence: 84%
“…Another study, using iPSCs from patients with bipolar disorder, showed further morphological alterations such as a decrease in the size of neurospheres and an increase in the length of their neurites. 152 However, a different study reported a decrease in the length of neurites and in the number of synapses in bipolar disorder–derived cells, compared with control iPSCs. 164 …”
Section: Defects In Neuronal Morphology and Interneuronal Connectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, ER calcium dynamics emerges as another major player. For example, store operated calcium entry (SOCE) is dysregulated in BD-induced pluripotent stem cells, leading to earlier neuronal differentiation and abnormal neurite outgrowth (81). Furthermore, altered expression of the miR-708-5p target Nnat has been associated with defective intracellular and ER calcium levels (33,74,82).…”
Section: Discussionmentioning
confidence: 99%